Activation of liver X receptors and retinoid X receptors prevents bacterial-induced macrophage apoptosis - Valledor, Annabel F. (National Academy of Sciences, 2004)
Microbe-macrophage interactions play a central role in the pathogenesis of many infections. The ability of some bacterial pathogens to induce macrophage apoptosis has been suggested to contribute to their ability to elude innate immune responses and successfully colonize the host. Here, we provide evidence that activation of liver X receptors (LXRs) and retinoid X receptors (RXRs) inhibits apoptotic responses of macrophages to macrophage colony-stimulating factor (M-CSF) withdrawal and several inducers of apoptosis. In addition, combined activation of LXR and RXR protected macrophages from apoptosis caused by infection with Bacillus anthracis, Escherichia coli, and Salmonella typhimurium. Expression-profiling studies demonstrated that LXR and RXR agonists induced the expression of antiapoptotic regulators, including AIM/CT2, Bcl-X(L), and Birc1a. Conversely, LXR and RXR agonists inhibited expression of proapoptotic regulators and effectors, including caspases 1, 4/11, 7, and 12; Fas ligand; and Dnase1l3. The combination of LXR and RXR agonists was more effective than either agonist alone at inhibiting apoptosis in response to various inducers of apoptosis, and it acted synergistically to induce expression of AIM/CT2. Inhibition of AIM/CT2 expression in response to LXR/RXR agonists partially reversed their antiapoptotic effects. These findings reveal unexpected roles of LXRs and RXRs in the control of macrophage survival and raise the possibility that LXR/RXR agonists may be exploited to enhance innate immunity to bacterial pathogens that induce apoptotic programs as a strategy for evading host responses.